Tinjauan Hukum Islam Terhadap Implementasi Akad dan Mekanisme Google Adsense dalam Bisnis Iklan - Luthfi, Ahmad Hashfi; Hidayatullah, Abdul Rahman Arif; Dewi, Nesfi Nurmiyarti; Saputra, Irham Yoga; Shinta, Septiana Has (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2021)
This study examines the mechanism of the Google Adsense contract in the advertising business against a review of Islamic law. The purpose of this study is to determine the process of implementing the google adsense mechanism in the advertising business against a review of Islamic law. This type of research uses data collection techniques from several journals obtained during the study by studying matters relating to the use of google adsense in the advertising business against a review of Islamic law. The results of this study indicate that the google adsense contract mechanism in the advertising business against a review of Islamic law reflects the basic values in accordance with the rules of contract law. keywords: Google Adsense; Advertising Business; Islamic Law.